Terrestrial carbon inputs drive methylmercury accumulation in zooplankton of boreal and subarctic lakes - Stephanie D. Graves; Karen A. Kidd; Michael T. Arts; Hans Fredrik Veiteberg Braaten; Heleen A. de Wit; Katrine Borgå; Staffan Åkerblom; Amanda E. Poste (Limnology and Oceanography, 2025)
Boreal and subarctic lakes are subject to the climate‐sensitive process of browning, whereby transport of terrestrial dissolved organic matter (tDOM) to lakes results in greater dissolved organic carbon (DOC) concentrations and associated darker water color. Increasing tDOM will increase mercury (Hg) transport to these lakes, but whether this leads to greater methylHg (MeHg) bioaccumulation in food webs remains unclear. We determined whether increasing DOC increased MeHg bioaccumulation in the lower food web (i.e., zooplankton) by measuring a suite of water chemistry characteristics (including aqueous MeHg and DOC) along with stable isotopes of C (δ 13 C) and N (δ 15 N), fatty acid (FA) profiles, and MeHg content of zooplankton from 16 Scandinavian boreal and subarctic lakes along a DOC gradient in the Fall of 2016. We found that both aqueous and zooplankton MeHg were positively correlated with DOC concentration, and that DOC and zooplankton MeHg both increased with the bacterial FA marker 18:1n‐7 and decreased with docosahexaenoic acid (DHA) : arachidonic acid and DHA : eicosapentaenoic acid ratios in zooplankton, which are indicators of diet or taxonomic composition. Zooplankton MeHg content was best predicted by δ 13 C and the FA 18:1n‐7, indicating that zooplankton MeHg bioaccumulation in zooplankton was associated with changes in their resource use along a DOC gradient. Our results suggest that lake browning will likely lead to an increase in MeHg bioaccumulation in zooplankton by affecting aqueous MeHg exposure and lower food web dynamics. In turn, this may lead to increased MeHg contamination in fish and other wildlife.

Seasonal patterns and environmental drivers of protistan plankton along a terrestrial–marine gradient in Isfjorden (Svalbard) - Anna Maria Dąbrowska; Maeve McGovern; Mikołaj Mazurkiewicz; Amanda Poste (Frontiers in Marine Science, 2025)
The Arctic is undergoing rapid environmental transformation, with intensified glacial and permafrost melt fundamentally altering freshwater discharge regimes and biogeochemical fluxes to coastal fjord systems. Here, we investigate how seasonal meltwater dynamics shape protistan plankton communities along a terrestrial – marine gradient in Isfjorden (Svalbard) during the exceptionally warm year of 2018. Sampling across three distinct melt season stages – pre-freshet (May), spring freshet (June), and late summer runoff (August) – revealed pronounced temporal and spatial shifts in community structure, strongly linked to evolving environmental gradients. In May, cold, clear, unstratified waters and marine nutrient inputs supported a typical late spring bloom, led by Phaeocystis pouchetii , which significantly contributed to the particulate organic carbon pool, and was followed by diatoms of the genera Chaetoceros and Thalassiosira . The June freshet triggered sharp stratification and nutrient enrichment from glacial and terrestrial sources, driving an unprecedented proliferation of small flagellates, notably Chrysochromulina and two morphologically distinct, yet unidentified taxa. However, by August, escalating turbidity from intensified meltwater inputs and sediment resuspension severely constrained photic conditions, suppressing protistan biomass despite sustained nutrient availability. Across the season, community dynamics were governed by complex interactions between nutrient supply, light limitation, and physical forcings such as stratification and advection. Our findings suggest that ongoing Arctic warming may increasingly favor opportunistic, small flagellates over traditional diatom-dominated blooms, with major implications for carbon cycling and food web dynamics in Arctic fjords.

Impacts of Changing Winters on Lake Ecosystems Will Increase With Latitude - Ted Ozersky; Amanda Poste; Milla Rautio; Eva Leu (Ecology Letters, 2025)
Climate warming is especially pronounced in winter and at high latitudes. Warming winters are leading to the loss of lake ice and changing snow cover on lakes. Historically, lake scientists have paid less attention to the ice cover period, leading to data and theory gaps about the role of winter conditions in lake ecosystem function and the consequences of changing winters. Here we use simple models to show that the latitudinal interaction between ice cover duration and light flux seasonality has profound and underappreciated implications for lakes. Our models focus on light and temperature, two key drivers of ecosystem processes. We show that the relative amount of light arriving in lakes during ice cover increases non‐linearly with latitude and that the light climate of high latitude lakes is much more sensitive to changing winter conditions than that of lower latitude lakes. We also demonstrate that the synchronicity between high light and warm temperatures may decrease with latitude, with implications for primary and secondary production. Our results suggest that ice loss may lead to greater relative change to productivity and biotic interactions in higher latitude lakes and also offer several testable predictions for understanding the consequences of climate‐induced changes across latitudinal gradients.

Nutrient fluxes from an Arctic seabird colony to the adjacent coastal marine ecosystem - Eirik A. Finne; Øystein Varpe; Joël M. Durant; Geir W. Gabrielsen; Amanda E. Poste (Polar Biology, 2024)
Seabirds are important vectors for nutrient transfer across ecosystem boundaries. In this seasonal study, we evaluate the impact of an Arctic colony (Alkhornet, Svalbard) of Black-legged Kittiwakes ( Rissa tridactyla ) and Brünnich’s Guillemots ( Uria lomvia ) on stream nutrient concentrations and fluxes, as well as utilization by coastal biota. Water samples from seabird-impacted and control streams were collected regularly throughout the melt season (June–September) for nutrient and organic carbon analysis. Stable carbon and nitrogen isotope analysis (δ 13 C and δ 15 N) was used to assess whether seabird-derived nitrogen (N) could be traced into filamentous stream algae and marine algae as well as consumers (amphipods). Concentrations of nitrate (NO 3 − ) and nitrite (NO 2 − ) peaked in July at 9200 µg N L −1 in seabird-impacted streams, 70 times higher than for control streams. Mean concentrations of phosphate (PO 4 3− ) in seabird-impacted streams were 21.9 µg P L −1 , tenfold higher than in controls. Areal fluxes from seabird-impacted study catchments of NO 3 − + NO 2 − and PO 4 3− had estimated ranges of 400–2100 kg N km −2 and 15–70 kg P km −2 , respectively. Higher δ 15 N was found in all biota collected from seabird-impacted sites, indicating utilization of seabird-derived nitrogen. Acrosiphonia sp. from seabird-impacted sites had higher δ 15 N values (20–23‰ vs. 3–6‰) and lower C:N ratios (10.9 vs. 14.3) than specimens collected from control sites, indicating reliance on seabird-derived nitrogen sources and potentially higher N-availability at seabird-impacted nearshore sites. Our study demonstrates how marine nutrients brought onshore by seabirds also can return to the ocean and be utilized by nearshore primary producers and consumers.

Seasonal riverine inputs may affect diet and mercury bioaccumulation in Arctic coastal zooplankton - Nathalie Carrasco; Maeve McGovern; Anita Evenset; Janne E. Søreide; Michael T. Arts; Sofi Jonsson; Amanda E. Poste (Science of The Total Environment, 2024)

Do DOM quality and origin affect the uptake and accumulation of lipid-soluble contaminants in coastal filter feeders? An experimental simulation of teflubenzuron exposure to blue mussels - Sabrina Schultze; Tom Andersen; Nina Knudtzon; Anders Ruus; Jan T. Rundberget; Steven J. Brooks; Amanda Poste; Dag O. Hessen; Katrine Borgå (Aquatic Toxicology, 2023)

Fifteen research needs for understanding climate change impacts on ecosystems and society in the Norwegian High North - Zina Kebir; Catherine Chambers; André Frainier; Vera Hausner; Ann Eileen Lennert; Jennifer Lento; Amanda Poste; Virve Ravolainen; Angelika H. H. Renner; David N. Thomas; Kerry Waylen (Ambio, 2023)
There is an urgent need to understand and address the risks associated with a warming climate for ecosystems and societies in the Arctic and sub-Arctic regions. There are major gaps in our understanding of the complex effects of climate change—including extreme events, cascading impacts across ecosystems, and the underlying socioecological dynamics and feedbacks—all of which need collaborative efforts to be resolved. Here, we present results where climate scientists, ecologists, social scientists, and practitioners were asked to identify the most urgent research needs for understanding climate change impacts and to identify the actions for reducing future risks in catchment areas in the Norwegian High North, a region that encompasses both Arctic and sub-Arctic climates in northern Norway. From a list of 77 questions, our panel of 19 scientists and practitioners identified 15 research needs that should be urgently addressed. We particularly urge researchers to investigate cross-ecosystem impacts and the socioecological feedbacks that could amplify or reduce risks for society.

Terrestrial Inputs Drive Seasonality in Organic Matter and Nutrient Biogeochemistry in a High Arctic Fjord System (Isfjorden, Svalbard) - Maeve McGovern; Alexey K. Pavlov; Anne Deininger; Mats A. Granskog; Eva Leu; Janne E. Søreide; Amanda E. Poste (Frontiers in Marine Science, 2020)

Stable isotope evidence from formalin–ethanol-preserved specimens indicates dietary shifts and increasing diet overlap in Lake Victoria cichlids - Mary A. Kishe-Machumu; Jacco C. van Rijssel; Amanda Poste; Robert E. Hecky; Frans Witte (Hydrobiologia, 2017)